Semiotic Analysis: Religious Values of “Batammat Kaji” In The Series of Traditional Malay Marriages in Asahan District - Hasibuan, Rial Sukma; Kholil, Syukur; Mailin, Mailin (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research aims to analyze the symbolic meaning and religius values contained in the “Batammat Kaji” ritual and how these values are communicated through symbols and ritual interactions. This research uses a qualitative approach with semiotic analysis methods. Data was obtained through observation, in-depth interviews and documentation studies. The research results revealed that the “Batammat Kaji” ritual contains symbols that represent the teachings of the Islamic religion and the beliefs of the local Malay community. The verbal and non-verbal communication processes that occur during rituals function to build social bonds, strengthen Malay cultural identity, and convey religius messages. Religius values, such as faith, piety and spirituality, are strongly integrated into every stage and element of the ritual, reflecting the efforts of Malay society to harmonize cultural traditions and Islamic religius teachings. The conclusion of this research provides a more comprehensive understanding of the religius values contained in the “Batammat Kaji” tradition and how these values are communicated through symbols and ritual interactions by the Malay community in Asahan Regency. These findings can contribute to Malay cultural studies, cross-cultural communication studies, and understanding of the integration of religion and tradition in society.